2013
DOI: 10.1002/pen.23733
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene glycol as an epoxy modifier with extremely high toughening effect: Formation of nanoblend morphology

Abstract: The brittle nature of epoxy polymers is one of their main drawbacks, preventing their widespread applications. In this research article, a new modifier with an extremely toughening effect on brittle epoxy was developed. It was found that introducing low-molecularweight polyethylene glycol (PEG) in the low amounts (up to 10%) into epoxy matrix considerably improves the impact and fracture properties of epoxy thermosetting polymer without attenuating its tensile properties. Epoxy/PEG hybrid containing 10% PEG ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 29 publications
(34 reference statements)
2
22
0
Order By: Relevance
“…As for these PEG modified products, epoxy vibration peaks at 1250, 915, and 830 cm −1 reflect that the PEG2000‐HBPAE sizing is an epoxy compound. The absorption peak at 3500 cm −1 belongs to the stretching vibration of hydroxyl group . It indicates that PEG has copolymerized with the HBPAE.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As for these PEG modified products, epoxy vibration peaks at 1250, 915, and 830 cm −1 reflect that the PEG2000‐HBPAE sizing is an epoxy compound. The absorption peak at 3500 cm −1 belongs to the stretching vibration of hydroxyl group . It indicates that PEG has copolymerized with the HBPAE.…”
Section: Resultsmentioning
confidence: 99%
“…As we know, as a popular material for modifying epoxy resins, polyethylene glycol (PEG) has a helical conformation along with a large amount of ether groups in its chain and two terminated hydroxyl groups, indicating a good compatibility with epoxy resin as well as outstanding hydrophilicity. Moreover, it should be noted that all PEGs have the advantage of environmental friendliness . Therefore, it is advisable and producible to prepare a series of PEG modified WEP sizing by adjusting molecular weight.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PEG alone is able to modify the properties of epoxy at higher loadings only (10 wt%) . To the best of our knowledge, there are no reports in the literature regarding the use of nanofiller‐grafted PEG in enhancing the properties of epoxy matrix.…”
Section: Introductionmentioning
confidence: 93%
“…These results suggest that the localization of PEO chains around the micelle core is an important design parameter. Zavareh and Samandari [181] recently reported a 2-to 3-fold increase in fracture toughness using a PEO modifier in epoxy at comparable concentrations. Even though a toughening mechanism was not suggested, the authors reported the formation of nano sized domains in the thermoset.…”
Section: Fig 18 (A)mentioning
confidence: 99%